Effectiveness of Face-to-Face and Online Learning Processes in the Package B Equivalency Program at PKBM Cahaya Ilmu Pekanbaru - Miranti, Tiara; Anwika, Yuka Martlisda; Fahmi, Rahmat (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The low level of public education and high dropout rates remain serious problems that require solutions through nonformal education pathways. This article aims to analyze the effectiveness of face-to-face and online learning in the Paket B Equivalency Program at PKBM Cahaya Ilmu Pekanbaru, along with its supporting and inhibiting factors based on the SNP Process Standards. A descriptive qualitative approach with a case study method was used, collecting data through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model with source and technique triangulation. Results show that face-to-face learning was moderately effective despite scheduling constraints among working learners, while online learning remained limited due to low digital literacy and unstable internet access. Overall, the learning process has not fully met SNP Process Standards, particularly in lesson planning, formative assessment, and supervision. Recommendations are given to the PKBM to strengthen a hybrid learning model and to the Pekanbaru City Education Office to improve guidance and digital access for nonformal education institutions.